Treatment of Perforating Veins - Review of Techniques - Costa Almeida, Carlos Eduardo Perdigão (Revista Portuguesa de Cirurgia; No 31 (2014): Número 31 - Dezembro 2014, 2014)
Introduction/Objectives: Incompetent perforating veins are implicated in venous ulcers and varicose veins recurrence. Complete  closure of all perforating veins is the only predictor of ulcer healing. Review and comparison of techniques to conclude on the best treatment  option is the objective of this article.  Methods: Open surgery, subfascial endoscopic perforator surgery (SEPS), percutaneous  ablation of perforating veins (PAP) (chemical and thermal) and embolization were analyzed and compared.  Results: Open surgery  has an ulcer-healing rate of 89% with recurrence of 23%. SEPS has an ulcer-healing rate of 90% and recurrence of 11%. Wound  complication rate with SEPS is 5%. Sclerotherapy has an ulcer healing rate up to 67,6%. PAP has near 100% immediate closure rate,  but decreases during follow-up.  Discussion: SEPS has better ulcer-healing rate, and decreases recurrence. The major disadvantage of  PAP is missed perforators, and long-term series are lacking. Conclusion: PAP is safe with minimal complications equal to SEPS, has  advantages compared to surgery, but there are no studies on ulcer-healing and recurrence rates. Due to that, SEPS continues to be  the choice/gold standard for the treatment of incompetent perforating veins. A combination of SEPS and PAP may result in better  outcomes.